Special issue: ICEA Public Policy Lesson conference, part of the After the Pandemic Conference Series - Konieczny, Jerzy (Review of Economic Analysis, 2022)
Papers in the special issue were presented at the Public Policy Lessons conference, the third conference in the After the Pandemic Conference Series, organized by the International Centre for Economic Analysis (ICEA) and held online, Nov 12-13, 2021.